SISTEM INFORMASI PEMESANAN BARANG DAN JASA PADA PT ROVINA JAYA SENTOSA - Erzi Hidayat; Alex Putra (ABEC Indonesia, 2023)
PT Rovina Jaya Sentosa is a company engaged in property and development that provides modern and energy-efficient residential places. Based on the interview results, this method of conveying the offered products is not efficient since it relies on oral communication. Therefore, a sales and service ordering information system is needed to attract clients’ interest and improve the image of PT Rovina Jaya Sentosa. In this research, a sales and service ordering information system has been developed for PT Rovina Jaya Sentosa using the waterfall method. The waterfall method is a sequential development approach, meaning the software development is carried out systematically and sequentially. This system provides information about the existence of PT Rovina Jaya Sentosa and the process of ordering products and services for its customers. The testing of the system using Black Box and User Acceptance Test (UAT) demonstrated that the functionality of the system runs well and meets user requirements. Additionally, the questionnaire testing results from 30 people who have used the system obtained an overall score of 87%, indicating that the Sales Information System at PT Rovina Jaya Sentosa is ready to be used by the public.   Keywords: Ordering System, PT Rovina Jaya Sentosa, Information System, Waterfall.